Réponses

2014-04-09T22:05:42+02:00
Bonsoir,

Pour le A, nous utiliserons la formule (a + b)² = a² + 2ab + b².

A=(5\sqrt{7}+2\sqrt{3})^2\\\\A=(5\sqrt{7})^2 + 2\times5\sqrt{7}\times2\sqrt{3}+(2\sqrt{3})^2\\\\A=5^2(\sqrt{7})^2 + 20\times\sqrt{21}+2^2(\sqrt{3})^2\\\\A=25\times7 + 20\sqrt{21}+4\times3\\\\A=175 + 20\sqrt{21}+12\\\\A=187 + 20\sqrt{21}

Pour le B, nous utiliserons la formule (a - b)² = a² - 2ab + b²

B=(3\sqrt{5}-4\sqrt{11})^2\\\\B=(3\sqrt{5})^2-2\times3\sqrt{5}\times4\sqrt{11}+(4\sqrt{11})^2\\\\B=3^2(\sqrt{5})^2-24\times\sqrt{55}+4^2(\sqrt{11})^2\\\\B=9\times5-24\sqrt{55}+16\times11\\\\B=45-24\sqrt{55}+176\\\\B=221-24\sqrt{55}

Pour le C, nous utiliserons la formule : (a - b)(a + b) = a² - b²

C=(3\sqrt{2}-5\sqrt{3})(3\sqrt{2}+5\sqrt{3})\\\\C=(3\sqrt{2})^2-(5\sqrt{3})^2\\\\C=3^2(\sqrt{2})^2-5^2(\sqrt{3})^2\\\\C=9\times2-25\times3\\\\C=18-75\\\\C=-57